Understanding Consumer Reactions to Offshore Outsourcing of Customer Services - Sharma, Piyush; Mathur, R.; Dhawan, A. (IGI Global, 2009)
Offshore outsourcing is a fast-growing aspect of the world economy today and it has drawn attention from policy makers as well as public at large in many developed countries. However, there is hardly any research on how outsourcing of customer services may influence individual consumers, their perceptions, attitudes and behaviors. In this chapter, the authors first review the extant literature in the country-of-origin and services marketing areas to highlight key concepts and theories relevant to this area. Next, they show how offshore outsourcing of customer services may influence consumer perceptions about service quality, brand image and brand loyalty on one hand and impact customer satisfaction, complaint behavior and repurchase intentions on the other. The role of several relevant demographic and psychographic variables is also discussed. Finally, the findings from a survey-based study among customers in three developed countries (US, UK and Australia) are reported along with a discussion of managerial implications and future research directions in this area.